Análise do gene MTHFR em relação à radiossensibilidade tumoral de pacientes com carcinoma epidermóide de cabeça e pescoço - Anders, Quézia (2014)
The enzyme methylenetetrahydrofolate reductase (MTHFR), responsible for the biological release of folate’s active form, may have reduced activity when polymorphic variants C677T and A1298C are present. Considering that folate participates in metabolic pathways that lead to nucleotide synthesis and methylation, these polymorphisms are relevant for the prognostic association with oral, oropharynx and larynx squamous cell carcinoma treated with radiotherapy or not. This study analysed polymorphisms C677T (rs1801133) and A1298C (rs1801131) as putative markers of tumor radiosensitivity. Our sample was made of 306 patients evaluated according to clinicopathological data, local disease relapse, death, disease specific survival, in relation to therapeutic option used in each case. Polymorphism were detected by PCR-RFLP. Survival curves were analysed according to the Kaplan-Meier model and its significance confirmed by the p of Wilcoxcon, being the error margin set to less than 5%. Associations between polymorphisms and local disease relapse, death and disease-free survival were not statistically significant. In contrast, MTHFR C677T patients with larynx SCC treated with radiotherapy showed that when at least T allele is present, there is a 3x decrease in the chance of early death. Therefore, this polymorphism may be an important biomarker for the prognostic evalution of larynx SCC patients treated with radiotherapy.